Canon EOS Rebel T1i / 500D For Dummies - King, Julie Adair (Hoboken, New Jersey John Wiley & Sons, Inc., 2009)
Veteran author Julie Adair King demystifies the high-end features of the new Canon T1i. The Canon EOS Rebel T1i is the newest camera offered in Canon's popular Rebel line of digital SLRs-and sells for less than 900. Packed with page after page of full-color images, this hands-on guide is aimed at helping you make the most of the Canon T1i's controls and shooting modes. Get ready to maximize the camera's main functions in order to create effective digital photos. Bestselling author Julie Adair King brings her expertise in the areas of digital cameras and photography and combines it with her fun.
Includes Index and Illustrations.
Keywords: Canon camera -- Handbooks, manuals